Financial Obstacles and Disadvantages of E-Learning From The Viewpoint of Dammam Teachers - Mayada Abu Alhomos; Nawal.H.Bahtiti; Tasneem Alayed; Omniya Miri (Indian Journal of Forensic Medicine & Toxicology, 2021)
The efforts of containing the novel virus (COVID-19) have begun to show signs of psychological impact onteachers and students across the globe. As a result of the COVID-19 pandemic, many school districts haveclosed for the remainder of the academic year. These closures are unfortunate because, for many students,schools are their only source of trauma-informed care and supports. When schools reopen, they mustdevelop a comprehensive plan to meet their students’ the potential mental health needs as social distancingand awareness campaigns can be a double-edged sword, if handled inadequately. This paper evaluated thechallenges of teachers in Dammam in e-learning during the period of the new coronavirus (COVID-19)global pandemic.